Epstein–Barr Virus Mucocutaneous Ulcer: An Unexpected Diagnosis of a New Entity - Howden, William; Kuo, Tony (Case Reports in Otolaryngology, 2021)
Epstein–Barr virus mucocutaneous ulcer (EBVMCU) is a new entity, only recently included in World Health Organisation classification of lymphoid neoplasms. Almost all cases described to date have been in patients with a predisposing risk factor of immunosuppression. This case presents a 21-year-old male admitted with tonsillitis and no overt immunosuppression, who is subsequently diagnosed with EBVMCU of likely iatrogenic origin.